Intelligent MPP tracker for photovoltaic systems under uniform irradiance and partial shading conditions - Oliveira, Paulo Daving Lima de (2018)
Photovoltaic systems for solar energy conversion are an attractive alternative in energy generation since the energy source – the solar resource – is widely available. Once the solar irradiance profile and the ambient temperature considerably vary along the daytime, for such systems to operate efficiently it becomes necessary to track the maximum power point (MPP) employing instruments that run algorithms conceived to this end. In this context, conventional techniques found in commercial tools nowadays perform this task satisfactorily when the entire photovoltaic system is subject to uniform irradiance and temperature conditions. Nevertheless, these algorithms reveal their drawbacks in the situations where irregular irradiance distribution occurs in the components of the system due mostly to the emergence of shadows, forcing the system to operate in a suboptimal power point. In addition to the lower efficiency, partial shading of the components may disrupt the conversion system, being, thereby, a phenomenon whose mitigation is of prominent importance. To avoid damaging the photovoltaic cells and/or modules when subject to such impairment, bypass diodes are inserted into the connection circuits of the components. The existence of these diodes modifies the power versus voltage curve (P-V curve) of the photovoltaic array, revealing multiple maxima, among which the desired global maximum power point (global MPP). The proposal herein presented consists in providing a computational intelligence-based algorithm that is capable of tracking the MPP at either uniform irradiance or partial shading conditions. Due to the compactness of the proposed algorithm, the implementation of the intelligent tracking system is highly suitable for low-cost serial processing devices. Simulation results point out the relevant ability of the system in tracking the MPP, being it unique or global, for several irradiance and temperature conditions.